The interindustry wage differentials by sector in China: What is the role of union density? - Li, Mingming (Frontiers in Sociology, 2022)
Although how union density affects interindustry wage differentials has long been discussed, there is a paucity of empirical research relevant to China. The trade-union system in China has been criticised for a long time because the Chinese Communist Party can influence union density and indirectly affect interindustry wage differentials through non-market mechanisms, such as administrative monopolies. This study explores the impact of union density on interindustry wage differentials in the context of administrative monopolies. The research takes a two-stage estimation approach after scrupulously integrating and conforming more than 40,000 individual data from the Urban Household Survey and various yearbooks from years 2004, 2008 and 2013. In the first stage, the individual wages are regressed with industry-sector dummies to obtain the wage-differential coefficients. Furthermore, union density is considered as a core variable to create regressions to the interindustry wage differential coefficients obtained in the first stage using administrative monopolies and labour safeguards as instrumental variables. It is found that although the union density was expected to increase wage differentials in industries, its influence diminished in three years under study. Administrative monopolies can indirectly affect wage differentials through union density. The support to grassroots unions in non-administrative monopolies industries and the opening up of industry to the private sector will help to overcome this dilemma.